Exposure of a patient with systemic lupus erythematosus, under immunosuppression therapy, to human immunodeficiency virus by accidental needlestick contamination - Oliveira, Ana Vanderley; da Mota, Licia M; Carvalho, Jozélio Freire; Araujo, Danilo Barral de; Santos-Neto, Leopoldo Luiz (Revista de Ciências Médicas e Biológicas, 2018)
Introduction: Systemic lupus erythematosus and infection by the human immunodeficiency virus are diseases that affect the immune system. There are few reported cases of the concomitance of both pathologies. Objective: To describe a clinical case of lupus who had a needlestick injury and had also HIV exposure. Method: Case report description. Results: A patient with lupus had a needlestick injury from an HIV positive patient. This person had several intolerances or side effects to retroviral prophylaxis, lupus flare was also observed; however, in the end of 24 weeks his serology was negative and viral load was also undetectable. Conclusion: This is the first case report of a patient diagnosed with SLE, using an immunosuppressive, exposed to HIV through a needlestick accident while working